A case study of using X-ray Thomson Scattering to diagnose the in-flight plasma conditions of DT cryogenic implosions - Poole, H; Cao, D; Epstein, R; Kasim, M; Vinko, S; Gregori, G; Regan, SP (AIP Publishing, 2022)
The design of inertial confinement fusion (ICF) ignition targets requires radiation-hydrodynamics simulations with accurate models of the fundamental material properties (i.e., equation of state, opacity, and conductivity). Validation of these models are required via experimentation. A feasibility study of using spatially-integrated, spectrally-resolved, X-ray Thomson scattering (XRTS) measurements to diagnose the temperature, density, and ionization of the compressed DT shell of a cryogenic DT implosion at two-thirds convergence was conducted. Synthetic scattering spectra were generated using 1-D implosion simulations from the LILAC code that were post processed with the X-ray Scattering (XRS) model which is incorporated within SPECT3D. Analysis of two extreme adiabat capsule conditions showed that the plasma conditions for both compressed DT shells could be resolved.